Article 8 TEU: towards a new generation of agreements with the neighbouring countries of the European Union? - Elsuwege, Peter van; Petrov, Roman A. (European Law Review, 2011)
Article 8 of the Treaty on European Union (TEU) provides a new legal basis for developing the European Union’s relations with its neighbouring countries. This contribution traces the origins of this provision and analyses its objectives and potential application in practice. It is argued that art.8 TEU codifies the conditionality approach of the European Neighbourhood Policy (ENP) and introduces a differentiation with traditional association agreements for political reasons. The launch of the Eastern Partnership in May 2009, including the offer of concluding association agreements with the European Union’s eastern partners, largely undermines the significance of this distinction. It is, however, not to be excluded that art.8 TEU is used in relation to other neighbouring countries which are not interested in formal association with the European Union.